Shape Memory Epoxy Resin and Its Composites: From Materials to Applications - Lan Luo; Fenghua Zhang; Jinsong Leng (Research, 2022)
Shape memory polymers (SMPs) have historically attracted attention for their unique stimulation-responsive and variable stiffness and have made notable progress in aerospace, civil industry, and other fields. In particular, epoxy resin (EP) has great potential due to its excellent mechanical properties, fatigue resistance, and radiation resistance. Herein, we focus on the molecular design and network construction of shape memory epoxy resins (SMEPs) to provide opportunities for performance and functional regulation. Multifunctional and high-performance SMEPs are introduced in detail, including multiple SMEPs, two-way SMEPs, outstanding toughness, and temperature resistance. Finally, emerging applications of SMEPs and their composites in aerospace, four-dimensional printing, and self-healing are demonstrated. Based on this, we point out the challenges ahead and how SMEPs can integrate performance and versatility to meet the needs of technological development.